EVALUATION PROGRAM OF THE FOOTBALL ATHLETE DEVELOPMENTS - Safiuddin, Safiuddin; Margono, Gaguk; Mardapi, Djemari (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2017)
The aims of this research was to know how far program of football athlete development was effectively successful, how was situation of sport school, whether input is complete supporting this program, whether outputs of this program produced properly without challenge and whether outcomes of this program regenerated correctly without matter, To evaluate this program properly and intensively, so it was used logic model program which consists of situation of sport school, input of this program, outputs of this program and outcomes of this program. Methodology of this research used technique of collecting data by observations, interviews, questionnaires, and documentations study. Analysis of collecting data use triangulation technique which gotten by data resources, namely; organizer/coach and staff of sport school, the athlete, athlete’s parents, and society. The results of this research was found and can be concluded that situation of sport school, input and outputs of this program have been being done fairly well, whereas outcomes of this program have been extended impact very well. Keywords: Athlete of Football, Sport School, Logic Model Evaluation Program